ANALISIS IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH TENTANG PELAYANAN KESEHATAN DI PUSKESMAS DAERAH TERPENCIL PERBATASAN DAN KEPULAUAN (DTPK) KABUPATEN SAMBAS KALIMANTAN BARAT - Noby Winarsa; Antono Suryoputro; Y Warella (Dian Nuswantoro Semarang, 2020)
Sambas District formulated a policy for the equality of health service in Primary Healthcare Centers of Remote And Underdeveloped Areas, Borderland, and Outlying Islands (CRUABOI) which are in the border between Indonesia and Sarawak-Malaysia. This study aimed to analyze the implementation of health service policy in the Primary Healthcare CRUABOI. This quantitative study was conducted in Primary Healthcare CRUABOI, Sambas District from June to July 2019. Data were taken through observation, document review, and in-depth interviews. Local government’s policy on health service delivery in Primary Healthcare CRUABOI, Sambas District did not run well. Some hindering factors of these conditions include communication among organizations, organizations’ human resources, disposition of implementors and bureaucratic structure. Community’s Rights to health service in Primary Healthcare CRUABOI, Sambas District have not been achieved. The central government shall predominantly fulfill health service needs in Primary Healthcare CRUABOI, Sambas District. The local government is expected to formulate more complex policy on health services in Primary Healthcare CRUABOI, Sambas District, such as conducting more socialization, allocating specific funds for CRUABOI, Sambas District, formulating SOP (Standard Operating Procedures) for CRUABOI, Sambas District, and improving coordination across sectors.Keywords: Policy, Goverment, CRUABOI, Sambas